Clevidipine for the management of hypertension in the perioperative cardiac and noncardiac surgical settings: a systematic review - Alice Bottussi; Jacopo D’Andria Ursoleo; Viviana Teresa Agosta; Enrica Piazza; Edoardo Mongardini; Fabrizio Monaco (Frontiers in Medicine)
IntroductionPerioperative hypertension is a common occurrence in anesthetic practice, potentially leading to cardiac complications resulting in unfavorable patient outcomes. Clevidipine emerges in the current drug scenario as an antihypertensive agent with advantageous properties like ultra-short half-life, titratable effect, and ease of use.MethodsA systematic search of PubMed/MEDLINE, EMBASE, Cochrane Central Register of Controlled Trials and Google Scholar databases was performed aided by a specific search string, to provide a synthesis of the available body of literature regarding clevidipine administration for the management of hypertension in the perioperative cardiac and noncardiac surgical settings.ResultsEighteen documents (summarizing data from 2,066 patients) published between 1997 and 2023 were included in the present review. Clevidipine was extensively compared to both placebo and other commonly used antihypertensive medications.DiscussionClevidipine demonstrated favorable efficacy and promising safety profiles. Moreover, it may represent a promising aid for the intraoperative management of hypertension, and a valuable addition to traditional antihypertensive drugs. However, significant gaps in research still persist, and further studies are warranted to better dissect its effects in frail populations and patients of different ethnicities.Systematic review protocolPROSPERO (CRD42024568584).